Eksperimen Pembelajaran Matematika dengan Strategi Problem Posing dan Problem Solving Terhadap Hasil Belajar Ditinjau dari Gaya Belajar Siswa Kelas VIII Semester Gasal MTs Negeri Surakarta 1 Tahun Ajaran 2016/2017 - Mafada, Arini Alfa, Prof. Dr. Sutama, M.Pd (2017)
On this research, there are three purposes. (1) examine the different effect of the implementation Problem Posing and Problem Solving toward mathematics learning outcomes, (2) examine the different effect of learning style of student toward mathematics learning outcomes, and (3) examine interaction between learning strategies and learning style of student towards mathematics learning outcomes. The type of this research is quantitative with quasiexperimental design. The population in this research is all students of VIII MTS N Surakarta 1 on academic year 2016/2017. Sample of this research consisted of two classes, they are experiment class and control class with the sampling technique that are use is cluster random sampling. Methods of data collection used documentation, questionnaires and tests. Techniques of analyzed used analysis of variance two paths with different cell with a significance level of 5%. Results of the data analysis was obtained: (1) there is a different effect between Problem Posing and Problem Solving toward mathematics learning outcomes, (2) there is no a different effect of learning style of student toward mathematics learning outcomes, and (3) there is no interaction between Problem Posing, Problem Solving and learning style of student towards mathematics learning outcomes.